The Overlapping Roles of Antimicrobial Peptides and Complement in Recruitment and Activation of Tumor-Associated Inflammatory Cells - Al-Rayahi, Izzat A. M.; Sanyi, Raghad H. H. (Frontiers in Immunology, 2015)
Antimicrobial peptides (AMPs) represent a group of small (6–100 amino acids), biologically active molecules, which are produced by plants, mammals, and microorganisms (1). An important element of the innate immune response, AMP, possesses potent antibiotic, antifungal, and antiviral activities. Furthermore, AMP may be involved in a number of other processes such as angiogenesis and modulation of the immune response such as stimulation of chemokines and chemotaxis of leukocytes. AMPs have been proposed as alternative therapies for infectious diseases. AMP may also exert cytotoxic activity against tumor cells. Further understanding of the biological function of these peptides during tumor development and progression may aid in the development of novel anti-tumor therapies with refined application of innate molecules. AMP and complement have distinct roles to play in shaping the microenvironment (Table 1). Components of the complement system are integral contributors in responding to infection and sterile inflammation. Moreover, complement plays a role in the trafficking of cells in the tumor microenvironment, and thereby possibly in the immune response to cancer. This article will try to outline characteristics of AMP and complement in mobilization and recruitment of cells in tumor microenvironment.